Evaluating the electronic tuberculosis register surveillance system in Eden District, Western Cape, South Africa, 2015. Issue 1 (1st January 2017) - Mlotshwa, Mandla; Smit, Sandra; Williams, Seymour; Reddy, Carl; Medina-Marino, Andrew
ABSTRACT: Background : Tuberculosis (TB) surveillance data are crucial to the effectiveness of National TB Control Programs. In South Africa, few surveillance system evaluations have been undertaken to provide a rigorous assessment of the platform from which the national and district health systems draws data to inform programs and policies. Objective : Evaluate the attributes of Eden District's TB surveillance system, Western Cape Province, South Africa. Methods : Data quality, sensitivity and positive predictive value were assessed using secondary data from 40, 033 TB cases entered in Eden District's ETR.Net from 2007 to 2013, and 79 purposively selected TB Blue Cards (TBCs), a medical patient file and source document for data entered into ETR.Net. Simplicity, flexibility, acceptability, stability and usefulness of the ETR.Net were assessed qualitatively through interviews with TB nurses, information health officers, sub-district and district coordinators involved in the TB surveillance. Results : TB surveillance system stakeholders report that Eden District's ETR.Net system was simple, acceptable, flexible and stable, and achieves its objective of informing TB control program, policies and activities. Data were less complete in the ETR.Net (66–100%) than in the TBCs (76–100%), and concordant for most variables except pre-treatment smear results, antiretroviral therapy (ART) and treatment outcome. The sensitivity of recorded variables in ETR.Net was 98% for gender, 97% for patient category, 93% for ART, 92% for treatment outcome and 90% for pre-treatment smear grading. Conclusions : Our results reveal that the system provides useful information to guide TB control program activities in Eden District. However, urgent attention is needed to address gaps in clinical recording on the TBC and data capturing into the ETR.Net system. We recommend continuous training and support of TB personnel involved with TB care, management and surveillance on TB data recording into the TBCs and ETR.Net as well as the implementation of a well-structured quality control and assurance system.